Beyond the one room school - Uhrmacher, P. Bruce; Bunn, Kristen E.; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
The purpose of this book is to showcase K-12 unique and educational significant activities that we may all learn from. The essays in the book, under girded by sound research, highlight remarkable activities that are already taking place around the world. The essays offer a detailed description of a classroom or a school; provide an interpretation of what is taking place in this setting and why; and inform readers about what can be learned from the setting. Some readers will appreciate the vivid descriptions, which will encourage them to push their own thinking. Others may learn from the author{u2019}s discussion of essential ideas from the essay, which can be reflected upon and transferred into other situations. All readers are likely to appreciate hearing about the varied and creative activities. The stories of these noteworthy teachers fall into four categories: risk-taking, creativity, care and community, and interconnectedness. Within these themes are ideas that teachers can use to create their own remarkable classrooms. Each theme is discussed and then several examples of how the theme plays out in the educational setting are described.
Electronic reproduction.
Keywords: School improvement programs -- United States; Classroom environment -- United States; Teacher effectiveness -- United States; Educational innovations -- United States; Electronic books